2021
DOI: 10.14744/ijmb.2021.02886
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Laboratory Employees Perception On Occupational Risk Factors

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License. Laboratory employees' perception of occupational risk factorsL aboratories can be a source of risk to employee health and safety. Safe working conditions are necessary for healthcare staff to remain healthy and provide good services [1]. Employees in hospitals and healthcare institutions face several sources of risk, including physical, chemical, biological, psychological, and ergonomic factors [2][3]. Physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Experience and knowledge in a particular field may affect a person's risk perception. The study conducted by Boyacı et al [28] examined the risk perception of laboratory workers in a hospital and found a significant relationship between the perception of risk and the length of time employed in the department. The highest risk perception was found in workers with 11-16 years of experience [28].…”
Section: Discussionmentioning
confidence: 99%
“…Experience and knowledge in a particular field may affect a person's risk perception. The study conducted by Boyacı et al [28] examined the risk perception of laboratory workers in a hospital and found a significant relationship between the perception of risk and the length of time employed in the department. The highest risk perception was found in workers with 11-16 years of experience [28].…”
Section: Discussionmentioning
confidence: 99%